Total hip arthroplasty for posttraumatic osteoarthritis secondary to acetabular fracture: An evidence based on 1,284 patients from 1970 to 2018 - Yuan, Qiling; Wang, Xinyi; Cai, Yongsong; Yang, Mingyi; Zheng, Haishi; Zhao, Xiaoming; Ma, Hongyun; Xu, Peng (Frontiers in Surgery, 2022)
Background Posttraumatic osteoarthritis (PTOA) can be a crippling sequela of acetabular fracture (AF), and total hip arthroplasty (THA) is often necessary to alleviate the clinical progression of symptoms. The purpose of this study was to summarize the existing clinical evidence concerning the surgical management of AF with THA through meta-analyses. Methods Databases were searched for articles published between 1995 and January 2022 that contained the keywords “acetabular,” “fracture,” “arthroplasty,” and “osteoarthritis.” Our study was registered in PROSPERO under number CRD42022314997. Results We screened 3,125 studies and included data from 31 studies with 1,284 patients. The median patient age at the time of THA was 52 years and ranged from 19 to 94 years. The pooled overall survival rate was 88% [86%–90%, 95% confidence interval (CI)] and could reach 83% at ≥15-year follow-up. For the Harris Hip Score, we pooled 22 studies with an overall mean difference of 43.25 (40.40–46.10, 95% CI; P < 0.001), indicating a large clinical effect. The pooled complications (incidence rates) across studies were: heterotopic ossification (22.53%), implant dislocation (4.66%), implant infection (3.44%), and iatrogenic nerve injury (1.07%). Conclusion THA in patients with PTOA following AF leads to significant improvement in symptoms and function at ≥15-year follow-up. Survival rates of implants free from re-operation or revision after THA decreased with follow-up time and could still reach 83% at ≥15-year follow-up. THA might be an effective therapeutic method for patients with PTOA due to AF.